Photocatalytic deposition of silver particles on titania nanotube thin films : Influence of precursor concentration - Kanakaraju, Devagi; Lim, Ying Pei; Lim, Ying Chin (UiTM, 2020)
Titania nanotubes (TiNT) has gained much interest as it has high surface area and fewer grain boundaries. In order to enhance the photoelectrochemical properties of TiNT, modification has been carried out to dope silver on TiNT. In this study, a combination of electrochemical anodisation and a photochemical reduction was employed to fabricate silver supported on titania nanotubes (AgTiNT). TiNT was synthesized via anodisation of titanium plate in a two-electrode system containing ethylene glycol and ammonium fluoride. Then, the silver particles were deposited on TiNT by immersion in various concentrations of silver precursor solution followed by ultraviolet light radiation. The prepared samples were characterized using field emission scanning electron microscopy (FESEM) for morphology, x-ray diffractometry (XRD) for crystal structure and energy dispersive x-ray (EDX) to determine the element content. TiNT demonstrated a well-ordered structure, but the nanotubes tend to clump together upon deposition of Ag. The effect of Ag deposition on the photoelectrochemical performance of TiNT was studied where almost one-fold enhancement in the photoelectrochemical property was observed for AgTiNT compared to pure TiNT.